STUDIES ON CHITOSAN - BENZALDEHYDE INTERACTION IN A HOMOGENEOUS SYSTEM AND ITS ADSORPTION BEHAVIOR OF METAL IONS IN AQUEOUS SOLUTION - Do Truong Thien; Nguyen Van Tuyen; Tran Thi Y Nhi (ASEAN Journal on Science and Technology for Development, 2008)
In this work, N-benzylidene chitosan was synthesized by chitosan –benzaldehyde interaction in a homogeneous system. The modified polymers were characterized by means of infrared (IR) spectra, X-Ray diffraction and thermal analysis. Their adsorption behavior was investigated by atomic absorption spectrophotometry. The experimental results showed that N-benzylidene chitosan had better adsorption properties and higher chemical resistance than that of chitosan.